AI-VoiceTherapy: An Automated Platform for Voice Rehabilitation Using Artificial Intelligence - Lachguer, Nisrine; Azizi, Ourda; El Mamoune, Soumaya (International Journal of Computer Engineering and Data Science (IJCEDS), 2025)
AI-VoiceTherapy is a mobile platform that leverages artificial intelligence to democratize access to speech therapy. The system uses OpenAI’s Whisper model to automatically detect and analyze speech disorders from voice recordings, including stuttering, dysphasia, dysarthria, and apraxia. Based on this analysis, the platform generates personalized therapy exercises tailored to the specific disorder and its severity. The three-tier architecture comprises an Android mobile application, a Spring Boot REST API, and a MySQL database. Key functionalities include automated speech analysis, personalized therapy generation, comprehensive progress tracking, and professional integration with speech-language pathologists. This innovation addresses geographical, economic, and resource barriers to traditional speech therapy, offering an accessible and scalable solution for millions affected by speech disorders worldwide.